Procedury koordynacji polityki budżetowej w krajach Unii Europejskiej i ich konsekwencje dla polityki gospodarczej - Baran, Bernadeta; Biegun, Krzysztof (Procedures of coordination of budgetary policy in EU countries and their consequences for economic policy, 2006)
One of the main aim, of the EU is strengthening the conditions for price stability and assuring strong and sustainable growth conducive to employment creation. In the opinion of many politicians and economists means safeguarding sound government finances is a solution. Fiscal discipline in the member countries of EU are provided by articles 99 and 104 of UE Treaty and regulations of the Stability and Growth Pact. They set two procedures: multilateral surveillance procedure and excessive deficit procedure, which enforce budgetary stabilization as a permanent feature of the EMU. The effective coordination of budgetary policies should ensure long-term sustainability, promote fiscal co-ordination and information sharing, and provide the flexibility to respond to shocks. It is argued that collective fiscal discipline and co-ordination are essential for a successful monetary union. Effective macroeconomic frameworks are those which are characterized by: credibility so that policymakers have public trust; flexibility allowing a prompt and timely response to economic developments; and legitimacy meaning there is widespread support for the framework.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 73-88